Mathematical Modeling of the Gas Dynamic Parameters of Impinging Heat-Transfer Medium Jet in Borehole Thermal Reaming Process - Bulat, A.F.; Voloshyn, O.I.; Potapchuk, I.Yu.; Yemelianenko, V.I.; Zhovtonoha, M.M.; Zhevzhyk, O.V.; Manigandan, S. (Наука та інновації, 2019)
Introduction. As compared with other ways of thermal destruction of rocks, the rock destruction by low temperature
plasma jet has advantage in terms of distribution of cracks in rock at a considerable depth, high heat transfer coefficient
and high specific heat flux, simplified system of automation and remote control, and compactness of thermal tool.
Problem Statement. Thus, the possibilities of analytical determination of optimal parameters of thermal effect on rocks
are limited by solution of thermoelasticity equations and contact problems of strength theory. Such formulation of the problem
is unacceptable due to complication of taking into account substantial changes in the physical and thermos-physical
rock properties while heating and applying mechanical load. Due to abovementioned facts it is obviously necessary to develop
a mathematical model that enables to define basic gas dynamic jet parameters of heat-transfer medium in the process
of borehole thermal reaming.
Purpose. The purpose of this research is to develop a mathematical model for calculating the gas dynamic characteristics
(pressure, density, and velocity) of the heat-transfer medium while it is moving along the surface of the borehole in the
thermal reaming process.
Materials and Methods. Mathematical modeling of the flow process for free and impact jets of heat-transfer medium
using a PC.
Results. Experimental studies have confirmed adequacy of the developed mathematical model for calculation of gas
dynamic characteristics (pressure, density, and velocity) of the heat-transfer while it is moving along the surface of the
borehole in the process of its thermal reaming.
Conclusions. The obtained results can be used for modeling the gas dynamic characteristics in the case of applying a
thermal tool with electric discharge in other technologies of heat treatment and destruction of materials. Вступ. Порівняно з іншими способами термічного руйнування гірських порід, руйнування породи за допомогою
струмини низькотемпературної плазми відрізняється поширенням тріщин в породі на значну глибину, високими
значеннями коефіцієнта тепловіддачі та питомого теплового потоку, спрощеною системою автоматизації та дистанційного управління, компактністю застосовуваного термоінструменту.
Проблематика. Можливості аналітичного визначення оптимальних параметрів термічного впливу на гірські
породи обмежені розв'язанням рівнянь термопружності та контактних задач теорії міцності. Така постановка задачі є
неприйнятною через складність врахування суттєвої зміни фізичних та теплофізичних властивостей гірських порід
в процесі їх нагрівання та механічного навантаження. Зважаючи на це, очевидною є необхідність розробки математичної моделі, яка дозволяє визначити основні газодинамічні характеристики струмини теплоносія в процесі термічного розширення свердловини.
Мета. Розробка математичної моделі розрахунку газодинамічних характеристик (тиск, густина, швидкість руху) теплоносія при його русі вздовж поверхні свердловини в процесі її термічного розширення.
Матеріали й методи. Математичне моделювання процесу течії вільної та імпактної струмини теплоносія з
використанням ПЕОМ.
Результати. Експериментальними дослідженнями підтверджено адекватність розробленої математичної моделі
розрахунку газодинамічних характеристик (тиск, густина, швидкість руху) теплоносія при його русі вздовж поверхні
свердловини в процесі її термічного розширення.
Висновки. Отримані результати можуть бути використані для моделювання газодинамічних характеристик при
застосуванні термоінструмента з дуговим електричним розрядом в інших технологіях термічної обробки та руйнування матеріалів. Введение. По сравнению с другими способами термического разрушения горных пород, разрушение породы
с помощью струи низкотемпературной плазмы отличается распространением трещин в породе на значительную
глубину, высокими значениями коэффициента теплоотдачи и удельного теплового потока, упрощенной системой
ав томатизации и дистанционного управления, компактностью термоинструмента.
Проблематика. Возможности аналитического определения оптимальных параметров термического влияния на
горные породы ограничиваются решением уравнений термоупругости и контактных задач теории прочности. Такая
постановка задачи является неприемлемой вследствие сложности учета существенного изменения физических и теплофизических свойств горных пород в процессе их нагревания и механического нагружения. В связи с этим очевидна
необходимость разработки математической модели, которая позволяет определить основные газодинамические характеристики струи теплоносителя в процессе термического расширения скважины.
Цель. Разработка математической модели расчета газодинамических характеристик (давление, плотность,
скорость движения) теплоносителя при его течении вдоль поверхности скважины в процессе ее термического
рас ширения.
Материалы и методы. Математическое моделирование процесса течения свободной и импактной струи теплоносителя с использованием ПЭВМ.
Результаты. Экспериментальными исследованиями подтверждена адекватность разработанной математической модели расчета газодинамических характеристик (давление, плотность, скорость движения) теплоносителя при его движении вдоль поверхности скважины в процессе ее термического расширения. Выводы. Полученные результаты могут быть использованы для моделирования газодинамических характеристик при применении термоинструмента с дуговым электрическим разрядом в других технологиях термической об работки и разрушения материалов.